Trumping Capacity Gap with Negotiation Strategies: the Mexican USMCA Negotiation Experience. (9th February 2020) - Bahri, Amrita; Lugo, Monica
ABSTRACT: In the past few months, we have witnessed the 'worst deal' in the history of the USA become the 'best deal' in the history of the USA. The negotiation leading to the United States–Mexico–Canada Agreement (USMCA) appeared as an 'asymmetrical exchange' scenario that could have led to an unbalanced outcome for Mexico. However, Mexico stood firm on its positions and negotiated a modernized version of North American Free Trade Agreement. Mexico faced various challenges during this renegotiation, not only because it was required to negotiate with two developed countries but also due to the high level of ambition and demands raised by the new US administration. This paper provides an account of these impediments. More importantly, it analyzes the strategies that Mexico used to overcome the resource constraints it faced amidst the unpredictable political dilemma in the US and at home. In this manner, this paper seeks to provide a blueprint of strategies that other developing countries could employ to overcome their negotiation capacity constraints, especially when they are dealing with developed countries and in uncertain political environments.